2016
DOI: 10.29063/ajrh2016/v20i2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early first Sexual Intercourse amongst Lesotho Women: Evidence from the 2009 Lesotho Demographic and Health Survey

Abstract: Age at first sexual intercourse may be a predictor of future sexual behaviour and an important indicator for exposure to HIV transmission. The purpose of the study is to establish risk factors associated with age at first intercourse among Lesotho women aged 15 to 49 years. The data used came from the 2009 Lesotho Demographic and Health Survey and probit models were applied for analysis. It was found that women who have had their first sexual intercourse at age 16 or below were at risk of being married at age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
4
4
2
Order By: Relevance
“…Men who had their first sex after adolescence stage had lower risk of STI compared to those who had their first sex during the adolescence stage. This finding supports findings from previous studies in China [16], Tanzania [17], Lesotho [18], Malawi [19], and in Republic of Korea [20]. Evidence in other parts of sub-Saharan Africa and Ghana suggest that adolescence period is one that is associated with several risky sexual behaviours including multiple sexual partners, experimenting with sex, sex without condom and alcohol use during sexual intercourse [15,21].…”
Section: Discussionsupporting
confidence: 88%
“…Men who had their first sex after adolescence stage had lower risk of STI compared to those who had their first sex during the adolescence stage. This finding supports findings from previous studies in China [16], Tanzania [17], Lesotho [18], Malawi [19], and in Republic of Korea [20]. Evidence in other parts of sub-Saharan Africa and Ghana suggest that adolescence period is one that is associated with several risky sexual behaviours including multiple sexual partners, experimenting with sex, sex without condom and alcohol use during sexual intercourse [15,21].…”
Section: Discussionsupporting
confidence: 88%
“…SAM in SSA who had their first sex below age 20 had higher odds of STIs than their counterparts who had their first sex after they were 20 years old. Several studies have reported similar findings in other countries: China [20,21], Lesotho [22], and Republic of Korea [23]. The plausible reason could be the risky sexual behaviors through experimentation often noted with adolescents.…”
Section: Synthesis With Previous Evidencesupporting
confidence: 54%
“…Although, one would expect that contextual differences could result in socialization that renders youth to initiate early sexual activities than others but our findings shows no significant effect of place of residence on early sexual experience after controlling for other variables. Our finding contradicts the findings of Odimegwu and Somefun (2017) in Nigeria, and the findings of Motsima and Malela-Majika (2016) in Lesotho. The insignificant finding in the adjusted hazard regression could be result of the fact that the effect of place of residence is confounded by other socioeconomic factors that affect early sexual experience.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, the study of Odimegwu and Somefun (2017) in Nigeria found that being a female youth from a rural area increased the risk of early sexual activities. Another study also found that women staying in a rural area is more at risk of early sexual experience compared to those staying in urban area (Motsima & Malela-Majika, 2016).…”
Section: Literature Reviewmentioning
confidence: 89%